2016
DOI: 10.5604/01.3001.0013.5417
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hair coat of the Polish Konik and Hucul pony focusing on the physical features and histological structure of different hair types

Abstract: The aim of the study was a comparative analysis of the hair coat of the Polish Konik and Hucul pony, focusing on the histological structure and physical parameters of the hair. Hair samples were obtained from 20 mares—10 of each breed. They were collected in winter, from the side of barrel, the mane, the tail, and front and rear fetlock. The hairs from the barrel were divided into overhair and underhair fractions. A higher percentage of underhair (about 70%) as compared to overhair (30%) was noted in both bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
3
3
2
Order By: Relevance
“…Hair from the mane was significantly thicker than several other body regions, at a median diameter of 110 μm. Although the prior study reported a percentage of outer hairs between 28% and 31% and of underhairs between 72% and 69% in the two breeds, respectively, our study showed the median percentage of outer hairs to be between 60% and 65% and underhairs between 40% and 35%, respectively.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…Hair from the mane was significantly thicker than several other body regions, at a median diameter of 110 μm. Although the prior study reported a percentage of outer hairs between 28% and 31% and of underhairs between 72% and 69% in the two breeds, respectively, our study showed the median percentage of outer hairs to be between 60% and 65% and underhairs between 40% and 35%, respectively.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, the differences of thin primary hair diameter and the reverse ratio of large and thin primary hair percentage reported here could be explained by the different seasons in which the two studies were performed (summer versus winter). Indeed, summer coat has been reported to be characterized by a lack of underhairs, supporting the lower percentage found in our study …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations